2006
DOI: 10.1097/01.fjc.0000197539.12685.f5
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Efonidipine on Aldosterone Synthesis and Secretion in Human Adrenocarcinoma (H295R) Cells

Abstract: Targeting aldosterone synthesis and/or release represents a potentially useful approach to the prevention of cardiovascular disease. Aldosterone production is stimulated by angiotensin II (Ang II) or extracellular K+ and is mediated mainly by Ca2+ influx into adrenal glomerulosa cells through T-type calcium channels. We therefore examined the effects of efonidipine, a dual T-type/L-type Ca2+ channel blocker, on aldosterone secretion in the H295R human adrenocarcinoma cell line; 100 nmol/L Ang II and 10 mmol/L … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 22 publications
2
46
0
Order By: Relevance
“…These findings were consistent with our recent in vitro study, which showed that efonidipine suppresses Ang II-and K + -induced aldosterone secretion from the human adrenocortical tumor cells (H295R), while nifedipine does not. These findings suggest that efonidipine suppresses aldosterone secretion through the blockade of T-type Ca 2+ channels (15). The present study is also consistent with earlier studies indicating that two other T-type Ca 2+ channel antagonists-mibefradil and tetrandrine-suppress aldosterone secretion from bovine adrenal glomerulosa cells (18,19).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…These findings were consistent with our recent in vitro study, which showed that efonidipine suppresses Ang II-and K + -induced aldosterone secretion from the human adrenocortical tumor cells (H295R), while nifedipine does not. These findings suggest that efonidipine suppresses aldosterone secretion through the blockade of T-type Ca 2+ channels (15). The present study is also consistent with earlier studies indicating that two other T-type Ca 2+ channel antagonists-mibefradil and tetrandrine-suppress aldosterone secretion from bovine adrenal glomerulosa cells (18,19).…”
Section: Discussionsupporting
confidence: 82%
“…Further, we confirmed that this action of efonidipine is attributed to the blockade of Ttype Ca 2+ channels (15). However, there have been few clinical reports on the role of Ca 2+ channel antagonists in reducing plasma aldosterone concentration.…”
Section: Introductionsupporting
confidence: 69%
“…8 Furthermore, T-type Ca channels are present in the adrenal glands and the results of a recent in vivo study have demonstrated that T-type CCBs inhibit aldosterone production in cultured adrenal cells. 9 However, there have been few clinical studies indicating the role of CCBs in reducing plasma aldosterone concentration in patients with CKD. Therefore, we considered that it would be intriguing to compare the effects of a T-type CCB and an L-type CCB on albuminuria and on the renin-angiotensin-aldosterone system in patients with CKD.…”
Section: Introductionmentioning
confidence: 99%
“…Both angiotensin II-and KCl-induced aldosterone secretion levels from human adenocarcinoma cells have been shown to be significantly attenuated by efonidipine, but not by nifedipine. 19 In patients with hypertension, efonidipine significantly reduced plasma aldosterone concentrations, whereas amlodipine did not. 20,21 In patients with chronic glomerulonephritis or with hypertension and nephropathy, not only proteinuria but also plasma aldosterone concentrations were significantly lower in those receiving efonidipine compared with those receiving amlodipine.…”
Section: Discussionmentioning
confidence: 99%